The Baltimore moment: race, place, and public disorder - Cobbina-Dungy, Jennifer (Journal of crime and justice, 2020)
The death of Freddie Gray in April 2015 sparked numerous protests and looting in Baltimore, Maryland. But why did massive uprising take place in Baltimore? What was so special about Baltimore that erupted into weeks of explosive incidents of race-based unrest, which garnered national attention? Using the Flashpoints Model of Public Disorder, this study examines the nature, causes, and dynamics of uprisings in the city of Baltimore, which lays the groundwork for understanding the conditions that can lead to future uprisings in other places. Systematic application of the Flashpoints Model shows that unrest in Baltimore was the result of a complex set of causal factors that ignited years of pent-up tension and highlights the significance of race as an organizing feature.